ONOMASTIC STUDY OF NICKNAMES AMONG WOMEN IN ANAM CULTURE (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This work investigates nicknames among women in Anam culture. It specifically focuses on the pragmatic and cultural meanings of those nicknames answered by Anam women in historic times. The onomastic theory and the conceptual metaphor theory were adopted in this research. Twenty women were purposively interviewed from four villages out of the eight villages of Anam. It was discovered that beauty, skills and personality are the forefront criteria for nicknaming Anam women. Secondly, the nicknames do not have patriarchal undertones. The nicknames invoke the pragmatic acts of complimenting because the nicknames given emerged from the cordiality between the name maker and the nicknamed. The nicknames answered portray the socio-cultural beliefs of the people. In addition, the nicknames are metaphorically laden with meanings like ‘Asamma’ (‘Asa’ is a shiny sweet fish, which metaphorically represents a beautiful woman), ‘Mmilinzu’ (‘mmili’ is a river, calm and peaceful. It means unperturbed beauty), ‘Mmilimma’ et cetera.  This is because the ‘Anamites’ are socio-culturally distinguished for their prowess in farming (agriculture, fishing and hunting): PERSONALITY IS A SIGNBOARD, WOMAN’S BEAUTY IS A TAR ROAD, WOMAN’S BEAUTY AS A RIVER, WOMAN’S FERTILITY IS A FERTILE YAM FARM, WOMAN AS AN EAGLE, WOMAN’S HUGENESS AS A HIPPOPOTAMUS, WOMAN’S BEAUTY IS AN ‘ASA’ (FISH), WOMAN’S GREATNESS AS ‘IJELE’ MASQUERADE, WOMAN’S NOBILITY IS AN ‘IROKO’ TREE AND WOMAN’S BEAUTY IS SPOTLESShe study, therefore, concludes by saying that the nicknames answered by Anam women reflect the people’s rich culture of farming, fishing, masquerade, ‘Ine Ezi’, ‘Ive Okpu’, Naming, Age grade, ‘Omugo’ et cetera.
Keywords: CognitiveMetaphor,Onomastics,Nicknames